Cardiac perfusion imaging using hyperpolarized 13c urea using flow sensitizing gradients. Issue 4 (20th May 2015) - Lau, Angus Z.; Miller, Jack J.; Robson, Matthew D.; Tyler, Damian J.
Abstract : Purpose: To demonstrate the feasibility of imaging the first passage of a bolus of hyperpolarized 13 C urea through the rodent heart using flow‐sensitizing gradients to reduce signal from the blood pool. Methods: A flow‐sensitizing bipolar gradient was optimized to reduce the bright signal within the cardiac chambers, enabling improved contrast of the agent within the tissue capillary bed. The gradient was incorporated into a dynamic golden angle spiral 13 C imaging sequence. Healthy rats were scanned during rest (n = 3) and under adenosine stress‐induced hyperemia (n = 3). Results: A two‐fold increase in myocardial perfusion relative to rest was detected during adenosine stress‐induced hyperemia, consistent with a myocardial perfusion reserve of two in rodents. Conclusion: The new pulse sequence was used to obtain dynamic images of the first passage of hyperpolarized 13 C urea in the rodent heart, without contamination from bright signal within the neighboring cardiac lumen. This probe of myocardial perfusion is expected to enable new hyperpolarized 13 C studies in which the cardiac metabolism/perfusion mismatch can be identified. Magn Reson Med, 2015. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.Magn Reson Med 75:1474–1483, 2016. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance.